The Regulatory Role of Non-coding RNA in Autophagy in Myocardial Ischemia-Reperfusion Injury - Wang, Dan; Niu, Zhenchao; Wang, Xiaolong (Frontiers in Pharmacology, 2022)
Following an acute myocardial infarction (AMI), thrombolysis, coronary artery bypass grafting and primary percutaneous coronary intervention (PPCI) are the best interventions to restore reperfusion and relieve the ischemic myocardium, however, the myocardial ischemia-reperfusion injury (MIRI) largely offsets the benefits of revascularization in patients. Studies have demonstrated that autophagy is one of the important mechanisms mediating the occurrence of the MIRI, while non-coding RNAs are the main regulatory factors of autophagy, which plays an important role in the autophagy-related mTOR signaling pathways and the process of autophagosome formation Therefore, non-coding RNAs may be used as novel clinical diagnostic markers and therapeutic targets in the diagnosis and treatment of the MIRI. In this review, we not only describe the effect of non-coding RNA regulation of autophagy on MIRI outcome, but also zero in on the regulation of non-coding RNA on autophagy-related mTOR signaling pathways and mitophagy. Besides, we focus on how non-coding RNAs affect the outcome of MIRI by regulating autophagy induction, formation and extension of autophagic vesicles, and the fusion of autophagosome and lysosome. In addition, we summarize all non-coding RNAs reported in MIRI that can be served as possible druggable targets, hoping to provide a new idea for the prediction and treatment of MIRI.